The Pepper RING Finger E3 Ligase, CaDIR1, Regulates the Drought Stress Response via ABA-Mediated Signaling - Joo, Hyunhee; Lim, Chae Woo; Han, Sang-Wook; Lee, Sung Chul (Frontiers in Plant Science, 2017)
Drought stress from soil or air limits plant growth and development, leading to a reduction in crop productivity. Several E3 ligases positively or negatively regulate the drought stress response. In the present study, we show that the pepper (Capsicum annuum) Drought Induced RING type E3 ligase 1, CaDIR1, regulates the drought stress response via ABA-mediated signaling. CaDIR1 contains a C3HC4-type RING finger domain in the N-terminal region; this domain functions during protein degradation via attachment of ubiquitins to the substrate target proteins. The expression levels of the CaDIR1 gene were suppressed and induced by ABA and drought treatments, respectively. We conducted loss-of-function and gain-of function genetic studies to examine the in vivo function of CaDIR1 in response to ABA and drought stress. CaDIR1-silenced pepper plants displayed a drought-tolerant phenotype characterized by a low level of transpirational water loss via increased stomatal closure and elevated leaf temperatures. CaDIR1-overexpressing (OX) Arabidopsis plants exhibited an ABA-hypersensitive phenotype during the germination stage, but an ABA-hyposensitive phenotype—characterized by decreased stomatal closure and reduced leaf temperatures—at the adult stage. Moreover, adult CaDIR1-OX plants exhibited a drought-sensitive phenotype characterized by high levels of transpirational water loss. Our results indicate that CaDIR1 functions as a negative regulator of the drought stress response via ABA-mediated signaling. Our findings provide a valuable insight into the plant defense mechanism that operates during drought stress.